2015
DOI: 10.3906/sag-1401-109
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of helmet and facial mask during noninvasiveventilation in patients with acute exacerbation of chronic obstructivepulmonary disease: a randomized controlled study

Abstract: Background/aim: Noninvasive mechanical ventilation (NIMV) is an approach to prevent complications in acute respiratory failure. In this study we aimed to compare the efficacy of a full face mask and a helmet in chronic obstructive pulmonary disease (COPD).Materials and methods: Fifty patients were divided randomly into 2 groups as full face mask (Group F) and helmet (Group H). Demographic data, forced expiratory volume at 1 s (FEV1), additional disease, hemodynamic parameters, respiratory rate, APACHE II score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The duration of noninvasive ventilation was relatively short in this study, although the duration was similar to a few related studies of NIV with a helmet 21,23 . This lower duration is because our hospital is located in an industrial area where many highways converge and construction sites abound, and which leads to multiple types of accidents.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The duration of noninvasive ventilation was relatively short in this study, although the duration was similar to a few related studies of NIV with a helmet 21,23 . This lower duration is because our hospital is located in an industrial area where many highways converge and construction sites abound, and which leads to multiple types of accidents.…”
Section: Discussionsupporting
confidence: 79%
“…Eye irritation was defined as excessive eye secretions, conjunctival congestion and edema, and any damage to the cornea or iris caused by the interface. Patients' tolerance was recorded at planned observation time points after beginning the study, and tolerance was evaluated using the following patient tolerance scale: poor, patients try to remove the mask or helmet; moderate, ventilation with a face mask or helmet is successful with suggestions for the patient; good, face mask or helmet use is slightly uncomfortable for the patients, but they want to use it; excellent, complete tolerance 21 . Nurses evaluated complications related only to skin care; clinical indicators such as ICU stay and patients' tolerance were assessed by doctors and the investigators.…”
Section: Ventilation Protocol Patients In Both Groups Received Noninmentioning
confidence: 99%
“…The continuous application of NIV was crucial in the onset phases of ARF, which otherwise might forebode NIV failure and life-threatening consequences [14, 4850]. It should be noted that this finding did not mean NIV with a helmet had no effect on the mortality of patients with hypercapnic ARF, since only two studies with small sample sizes had reported this variable in this meta-analysis [20, 30]; this question warrant further investigation.…”
Section: Discussionmentioning
confidence: 90%
“…Finally, 11 studies involving 621 patients, with six RCTs [15, 16, 2932] and five case-control studies [14, 17, 20, 33, 34], were included for the meta-analysis. These studies recruited patients admitted to ICUs [14, 15, 20, 2932, 34], emergency departments [33], high dependency units [16], and departments of hematology [17] in different countries: Italy [1417, 20, 34], Turkey [29, 30], Brazil [31], America [32], and France [33]. The characteristics of the studies are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…After reviewing, 18 studies were excluded for the following reasons: non-RCT (n = 6) [18][19][20][21][22][23], review article (n = 5) [24][25][26][27][28], subjects were infants (n = 3) [29][30][31], subjects were healthy volunteers (n = 2) [32,33], animal trial (n = 1) [34] and news (n = 1) [35]. Finally, seven English studies [9][10][11][12][36][37][38] and five Chinese studies [39][40][41][42][43] matched the inclusion criteria and were suitable for our meta-analysis. The flow diagram in Fig 1 details the selection process.…”
Section: Study Selectionmentioning
confidence: 99%